Influence of Resilience and Optimism on Distress and Intention to Self-Isolate: Contrasting Lower and Higher COVID-19 Illness Risk Samples From an Extended Health Belief Model - Cervera-Torres, Sergio; Ruiz-Fernández, Susana; Godbersen, Hendrik; Massó, Lena; Martínez-Rubio, David; Pintado-Cucarella, Sheila; Baños, Rosa M. (Frontiers in Psychology, 2021)
The study investigated the influence of resilience and dispositional optimism on, first, emotional distress and, second, the intention to self-isolate, experienced by people with a lower and higher illness risk, during the lockdown imposed in Spain during the first COVID-19 wave. These effects were investigated against the background of the Health Belief Model (HBM). A convenience sample of N = 325 participants completed an online survey including an ad-hoc questionnaire measuring the HBM core factors: Perceived health threat (susceptibility and severity of getting infected), and perceived quarantine benefits and costs. Self-efficacy and perceived social pressure were also measured. Based on reviews regarding pandemic outbreaks, quarantine benefits were conceptualized as the perceived effectiveness and solidary contribution of self-isolating in line with the quarantine protocols. Quarantine “psychosocial” costs were conceptualized as a composite of perceived boredom, loneliness, and economic concerns. Findings revealed an asymmetrical pattern of results so that (i) people at higher risk were more distressed by the perceived severity of getting infected whereas people at lower risk were more distressed by the psychosocial costs. Moreover, (ii) resilience and optimism were more “protective” against distress within the lower and higher risk groups, respectively. In addition, (iii) quarantine benefits and self-efficacy promoted the intention to self-isolate within both groups. However, (iv) optimism hindered such intention. This finding is discussed in the light of links between dispositional optimism and optimistic bias; the underestimation of experiencing negative events, which can relax the perceived health risk. Based on these findings, communication campaigns should prioritize information about the effectiveness of the implemented preventive behaviors rather than the costs of not implementing them, and be cautionary in encouraging excessive optimism.